Modulating Iron for Metabolic Support of TB Host Defense - Phelan, James J.; Basdeo, Sharee A.; Tazoll, Simone C.; McGivern, Sadhbh; Saborido, Judit R.; Keane, Joseph (Frontiers in Immunology, 2018)
Tuberculosis (TB) is the world’s biggest infectious disease killer. The increasing prevalence of multidrug-resistant and extensively drug-resistant TB demonstrates that current treatments are inadequate and there is an urgent need for novel therapies. Research is now focused on the development of host-directed therapies (HDTs) which can be used in combination with existing antimicrobials, with a special focus on promoting host defense. Immunometabolic reprogramming is integral to TB host defense, therefore, understanding and supporting the immunometabolic pathways that are altered after infection will be important to the development of new HDTs. Moreover, TB pathophysiology is interconnected with iron metabolism. Iron is essential for the survival of Mycobacterium tuberculosis (Mtb), the bacteria that causes TB disease. Mtb struggles to replicate and persist in low iron environments. Iron chelation has therefore been suggested as a HDT. In addition to its direct effects on iron availability, iron chelators modulate immunometabolism through the stabilization of HIF1α. This review examines immunometabolism in the context of Mtb and its links to iron metabolism. We suggest that iron chelation, and subsequent stabilization of HIF1α will have multifaceted effects on immunometabolic function and holds potential to be utilized as a HDT to boost the host immune response to Mtb infection.